2020
DOI: 10.7717/peerj.9891
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between individual phenotype and the division of labour in naked mole-rats: it’s complicated

Abstract: Background The naked mole-rat (Heterocephalus glaber) is among the most social mammals on the planet, living in eusocial groups of up to 300 individuals that contain a single reproductive female and up to three reproductive males. A critical aspect of their complex social system is the division of labour that allows non-breeders to form an effective workforce. Age- or weight-based polyethisms are widely cited as explanations for how labour is divided, but evidence in support of these hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 64 publications
7
23
0
Order By: Relevance
“…Our data reveal that sex differences in work-related cooperative behaviour of naked mole-rats are minor and body mass and age-related patterns are broadly similar in male and female non-breeding individuals. This is consistent with previous studies (Jarvis et al 1991, Lacey and Sherman 1997, Gilbert et al 2020), and it is possible that as in other social mole-rats species, sex-differences are limited to allo-parental care behaviour which we were unable to record in this study (Bennett 1990, Zöttl et al 2016a, Thorley et al 2018, Zöttl et al 2018). The lack of sex-differences contrasts with the distribution of cooperative behaviours in many other cooperatively breeding species where sex differences are common and often linked to sex differences in philopatry (Clutton-Brock et al 2002).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data reveal that sex differences in work-related cooperative behaviour of naked mole-rats are minor and body mass and age-related patterns are broadly similar in male and female non-breeding individuals. This is consistent with previous studies (Jarvis et al 1991, Lacey and Sherman 1997, Gilbert et al 2020), and it is possible that as in other social mole-rats species, sex-differences are limited to allo-parental care behaviour which we were unable to record in this study (Bennett 1990, Zöttl et al 2016a, Thorley et al 2018, Zöttl et al 2018). The lack of sex-differences contrasts with the distribution of cooperative behaviours in many other cooperatively breeding species where sex differences are common and often linked to sex differences in philopatry (Clutton-Brock et al 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Mole-rats within the genera Fukomys and Cryptomys show body size related changes in cooperative behaviour and individuals can vary widely in the frequency of burrowing behaviour (Bennett and Jarvis 1988, Bennett 1990, Burda 1990, Bennett 1992, Jarvis et al 1994, Spinks et al 1999, Scantlebury et al 2006). However, longitudinal studies of Damaraland mole-rats of known ages have shown that individuals do not trade-off investment in cooperative behaviours and that the general patterns of the distribution of cooperative behaviour across individuals are similar to those of naked mole-rats shown in this study (Zöttl et al 2016a, Thorley et al 2018, Zöttl et al 2018, Gilbert et al 2020). Evidence from field studies of other Fukomys species also supports the notion that the behavioural similarity of mole-rats societies with obligatorily eusocial insects has probably been overemphasized in the past and evidence for specialisation, divergent developmental trajectories or bimodal trait distributions across individuals are rare (Faulkes and Bennett 2016, Šklíba et al 2016, Zöttl et al 2016b, Van Daele et al 2019, Voigt et al 2019).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Subordinates are suppressed from releasing sex steroid hormones due to the antagonistic behavior of the queen, which results in delayed puberty and therefore individuals live under a hypogonadic condition (Pinto et al, 2010). Several studies on humans and laboratory rodents have revealed that hypogonadism results in suboptimal skeletal development and may lead to an increased risk of bone fractures later in life (Golden & Carlson, 2008;Pinto et al, 2010;Yingling & Taylor, 2008).…”
Section: Introductionmentioning
confidence: 99%